Propuesta de desarrollo agroturístico a través de productos con identidad territorial (PIT) en la parroquia Chuquiribamba, cantón Loja. - Benítez Cango, Génessis Anahi (2022)
In Chuquiribamba, a rural parish of the Loja canton, called cultural heritage of Ecuador, this research work was developed and the general objective was: "Propose a model of agrotourism development through products with territorial identity (PIT) in the rural parish Chuquiribamba.” For this, three specific objectives were proposed, which allowed the general objective to be fulfilled. The first objective was "To carry out a diagnosis of the situational agro-tourism potential of the Chuquiribamba parish, Loja canton.", The second objective was "To establish agro-tourism development strategies for the Chuquiribamba parish, Loja canton", and as a last "To carry out a management model for the development of PIT agrotourism in the Chuquiribamba parish”. The study of the first objective was divided into four phases. The first was the gathering of information on the products with territorial identity (PIT) present in the territory through IICA's guide for the design of agrotourism products and the holding of a participatory workshop with the actors involved. The second phase was the diagnosis of the territory by components through dimensions: economic, social, environmental, and political-institutional dimensions, based on the information provided by the Territorial Development and Planning Plan (PDOT) of the Chuquiribamba parish 2015-2019. The third phase was the analysis of the offer that included the study of the attractions, through the tourist inventory cards of the Ministry of Tourism (MINTUR); the information on the tourist offer of the Chuquiribamba parish was collected with the matrix of the community diagnosis of Carla Ricaurte Quijano and the offer of agrotourism farms of the parish where the technique of interviewing owners of plots/land with potential for the development of agrotourism. Finally, the demand analysis was carried out where the PEA(active economic population) of the city of Loja was taken into consideration, with a total of 208 surveys. For the second objective, a SWOT and crossed SWOT analysis was carried out, and finally a matrix of specific strategies to develop and promote agrotourism and the PITs present in the Chuquiribamba parish. Finally, in the third objective, the model proposed by the guide for the design of agrotourism products by Marvin Blanco and Hernando Riveros was taken, which consists of a destination management organization structure (OGD), legal support, company principles and values, and, a working plan. In the results, the main PITs were determined in the assigned categories, such as agricultural PITs: attack, agro-industrial PITs: "La Lojana" horchata factory and "Doña Gloria" vineyard, 5 gastronomic PITs: Cakes and handicrafts PITs: Woven on a loom with lamb's wool yarn. In the same way, strategies focused on the dissemination of knowledge in the population focused on the PITs and the management model that involves public and private actors that will work together for the fulfillment of the objectives where the development management is carried out agrotourism as an opportunity to boost the economy and well-being of its inhabitants. Among the main conclusions, it was determined that the Chuquiribamba parish has PIT in all the assigned categories, being the most outstanding PIT in the place, without a doubt, the horchata company "La Lojana" since it is a traditional drink with cultural roots and tradition in the Chuquiribamba parish